Goya's Glass - Zgustová, Monika (Book collections on Project MUSE., 2012)
The Duchess of Alba, known as Goya's muse, recalls the passions of youth on her deathbed in the royal court of eighteenth-century Madrid. A young woman defies the protocols of her arranged marriage and pursues love--and the life of a published writer--until her readers condemn her as a danger to society in the Austro-Hungarian Empire. Nina Berberova escapes persecution during the Russian Revolution and flees to Paris, where the intelligentsia naïvely covet the promise of a Soviet Union. These three women attempt to find passion and intimacy in worlds that rarely accommodate female desire.